Development of Debris flow Vulnerability Curve for Data-driven Method - Song Chang-Ho; Lee Ji-Sung; Nguyen Ho-Hong Duy; Ha Yong-Soo; Kim Yun-Tae (E3S Web of Conferences, 2023)
Various landslide disasters due to abnormal climate are increasing all over the world, and the inflow of debris flow is causing great damage to human life and social infrastructure. As such, in order to preemptively respond to debris flow, it is necessary to conduct a vulnerability assessment of the hazardous area based on the vulnerability curve. Therefore, in this study, the hazard intensity (depth, velocity, and impact pressure of debris flow) was analysed by performing back analysis using the DAN3D numerical model for 27 debris flow disaster areas in Korea from 2011 to 2020. And the vulnerability curve for the building was developed through the relationship between the degree of damage to the building and the impact pressure obtained through the case analysis of debris flow disasters.